Pengaruh Model Pembelajaran Bamboo Dancing Terhadap Hasil Belajar IPS Di Kelas V SD NEGERI 50 Kuranji Padang - Silfi Melindawati (Universitas Negeri Padang, 2019)
This research is motivated by the low student learning outcomes in social studies learning in the fifth grade of SDN 50 Kuranji Padang. This study aims to determine the effect of the Bamboo Dancing learning model on the learning outcomes of fifth grade students of SDN 50 Kuranji Padang. The research method used was Quasi Experimental Design with the design of Posttest Only Control Design. The population in this study were fifth grade students of SDN 50 Kuranji Padang, which class VB using the Bamboo Dancing learning model while the VA class using the Bamboo Dancing learning model. Based on the results of the posttest, the average value of the experimental class is 80.0 and the average value of the control class is 63.93. From the results of hypothesis testing with a significance level of 0.05, obtained a significant value of 0.51 because sig˃α, the hypothesis is accepted, so it can be concluded that the Bamboo Dancing learning model influences social studies learning outcomes of students in fifth grade SDN 50 Kuranji Padang in the 2018 school year / 2019.